Driving Policy Impact: Changing government thinking - Thomson, Sarah; Green, Anja-Maaike (International Journal of Population Data Science, 2025)
Objectives The presentation will consider: How to engage effectively with government on your research Routes into government, how to interact with policy and analytical systems, including Areas of Research Interest Different types of effective policy impact Methods The workshop will cover practical tips on how to achieve policy impact. The session will include a short presentation from the ADR Scotland Engagement and Impact team and potential interview style input from a SCADR researcher on successful research impact on policy (TBC). Results ADR Scotland Engagement and Impact team will highlight the range of routes and focus on one or two aspects of their work including ADR Scotland Data with Impact series which supports collaboration between government and academia. The SCADR researcher (TBC) will outline research undertaken, how this was impactful and how this was achieved. Conclusion Outputs will include provision of top tips on achieving policy impact across a range of contexts including practical sources of support.